Health cadres empowerment program through smartphone application-based educational videos to promote child growth and development - Friska, Dewi; Kekalih, Aria; Runtu, Fergie; Rahmawati, Andini; Ibrahim, Naufal Arkan Abiyyu; Anugrapaksi, Eghar; Utami, Nindya Permata Bunda Surya; Wijaya, Alya Darin; Ayuningtyas, Rathia (Frontiers in Public Health, 2022)
Indonesia’s health care system relies on non-health professionals called cadres to operate child health promotion programs in the Public Health Centre (Puskesmas). Despite this effort, the child malnutrition rate remains high. This study was aimed to identify and develop health promotion media that can assist health cadres in promoting child health. This study was divided into three-phase. The first phase was the need assessment using focus group discussion and knowledge, attitude, and practice (KAP); the second phase is video development, which involves medical students, general practitioners, pediatricians, and health promotion experts; and the third phase was video viewing by cadres and post-viewing tests for health cadres. A comparison of pre-test and post-test participants’ total scores was performed with the student's T-test. Need assessment showed that the knowledge of the cadres needs improvement and there was a need for proper educational media material that can be used by the Puskesmas. Five videos were produced, four videos were about children’s nutritional intake recommendations during four different age groups and one video was about the information and invitation to come to Integrated Health Service Post (Posyandu). There was a significant improvement from pre-test total scores to post-test total scores (p < 0.001). Smartphone application-based educational videos are effective and reliable child health promotion media for Puskesmas staff and parents.